Dengue ay supilin, komunikasyon sa programa ating suriin a quasi-experimental study to describe the response of Quezon City residents to the communication strategies of Quezon City Dengue Prevention and Control Program (QCDPCP) - Quilang, Rianne Clarisse A. 1993; Tolentino, Feliz Marie B. (2014)
This study described the response of Quezon City residents - particularly Barangay Kamuning - to the communication strategies of Quezon City Dengue Prevention and Control Program (QCDPCP). It focused more on the communication used that led to possible changes in residential awareness, knowledge, attitude and behavior parallel to the objectives of the Program. Accomplished under a quasi-experimental research design with survey as its main method, this study made use of both quantitative and qualitative approaches in determining the triangulation among factors such as the Program's message and media used, communication strategies, as well as the residential response to the Program's suggestive control and prevention strategies. Findings reveal that Television is the reesidents' main source of dengue information and supplemented by other dengue message channels. However, residents are not able to critically distinguish QCDPCP from the national program as well as from other sources of dengue information either mediated or interpersonal. Nevertheless, the dengue program is still an indispensable tool for reinforcing dengue literacy and promoting the practice of dengue prevention."